2018
DOI: 10.3389/fpls.2018.00677
|View full text |Cite
|
Sign up to set email alerts
|

Rational Application of Fertilizer Nitrogen to Soil in Combination With Foliar Zn Spraying Improved Zn Nutritional Quality of Wheat Grains

Abstract: To alleviate human zinc (Zn) deficiency, it is worthy to develop rational agronomic managements to achieve high yielding and high resource-use efficiency wheat (Triticum aestivum L.) grains biofortified with Zn. Effects of application of three rates of nitrogen (N) fertilizer (75,200 and 275 kg·ha−1) to soil in combination with three foliar applications (deionized water, Zn alone, and a combination of Zn and sucrose) on grain yield, yield components, grain Zn concentration, protein, phytic acid (PA), phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 67 publications
3
35
5
Order By: Relevance
“…In the current study, foliar Zn and/or sucrose applications did not affect the yield or other agronomic traits of maize in Quzhou and Licheng (Tables 3 and 4), suggesting that the dry-matter accumulation in maize grains is less dependent on exogenous foliar Zn and/or carbohydrate supply, at least under the conditions used in this study. Similar results were previously reported for maize and wheat under pot or field conditions [3,26,27,35,38,50,51]. For Zn, this finding may be attributed to the high Zn concentration in soil and the suitable soil conditions, and thus the good Zn nutritional status of plants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, foliar Zn and/or sucrose applications did not affect the yield or other agronomic traits of maize in Quzhou and Licheng (Tables 3 and 4), suggesting that the dry-matter accumulation in maize grains is less dependent on exogenous foliar Zn and/or carbohydrate supply, at least under the conditions used in this study. Similar results were previously reported for maize and wheat under pot or field conditions [3,26,27,35,38,50,51]. For Zn, this finding may be attributed to the high Zn concentration in soil and the suitable soil conditions, and thus the good Zn nutritional status of plants.…”
Section: Discussionsupporting
confidence: 88%
“…In 1953, it was reported that the addition of sucrose to urea sprays reduced the injury of maize leaves, perhaps by reducing the rate of urea absorption and increasing the rate of urea translocation within the plant [62]. In our previous studies, foliar application of sucrose + Zn was associated with greater improvements in the concentration, content, and bioavailability of Zn in wheat (a C3 plant) than the spraying of Zn only [3,35]. As mentioned by Zhao et al (2014) [51], the relatively higher effectiveness of sucrose + Zn may be attributed to (1) the longer drying time of the spraying solution;…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The application of Zn can simultaneously increase crop yield and grain Zn content under limited soil Zn availability (Drissi et al 2015;Dimkpa et al 2017aDimkpa et al , b, 2018bDimkpa et al , 2019a. Grain Zn content can be more than doubled, even under sufficient Zn soil supply, through foliar Zn application, while grain P or phytate content is not, or only modestly, affected (Zhang et al 2012;Khan et al 2018;Xia et al 2018). As such, foliar Zn fertilization can significantly reduce the PA/Zn molar ratio and increase the bioavailability of both Zn and P. Wang et al (2015) demonstrated a marked reduction in PA/Zn ratio from over 30 in the control treatment to below 15 with Zn fertilization.…”
Section: Approaches To Improve Nutritional Quality By Reducing Phytatmentioning
confidence: 99%
“…Zn supply is a direct and effective method to solve the low availability of Zn in soil ( Almendros et al, 2013 ; Guo et al, 2015 ). Furthermore, nitrogen (N) application or N combined with Zn application is beneficial for increasing Zn concentration, enhancing Zn translocation to grain in wheat, especially when wheat is cultured in Zn-deficient soil ( Kutman et al, 2010 ; Li et al, 2015 ). N combined with Zn application can enhance Zn uptake via membrane transport and stimulate root development ( Nie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%